Protective Factors Affecting Successful Resilience in Intimate Partner Violence: A Systematic Review - Aisyah Nurul Hafidah; Ilham Nur Alfian (Universitas Aisyah Pringsewu, 2022)
This literature review identified five articles to show the information about the protective factors that can help women victims of intimate partner violence to attain a state of resilience. A systematic review of studies in resilience in women victims of intimate partner violence. With inclusion and exclusion criteria; English language peer-reviewed articles; studies focusing on resilience in victims of IPV; studies conducted on women participants. The review findings indicated that the most mentioned protective factors in helping IPV victims to attain resilience are abusive behavior awareness and formal or informal social support. Abstrak: This literature review identified five articles to show the information about the protective factors that can help women victims of intimate partner violence to attain a state of resilience. A systematic review of studies in resilience in women victims of intimate partner violence. With inclusion and exclusion criteria; English language peer-reviewed articles; studies focusing on resilience in victims of IPV; studies conducted on women participants. The review findings indicated that the most mentioned protective factors in helping IPV victims to attain resilience are abusive behavior awareness and formal or informal social support.